Enhancing Flow Properties and Preventing Sticking and Picking in Tablet Formulations: Exploring the Efficacy of StarTab® as a Multifunctional Additive - Sandeep Kumar (University of Huddersfield Press, 2023)
This study investigates the flow and compression behaviour of four excipients (StarTab®, MCC, Mannitol, Lactose) when combined with caffeine as a model drug for direct compression. Notably, pure caffeine particles demonstrate high adhesion to punch and die walls. However, the incorporation of StarTab®led to improved flow of the pre-blend, along with reductions in detachment stress (DS) and ejection stress (ES) during tabletting. Contrarily, blending caffeine with MCC, Mannitol, and Lactose did not result in considerable improvements in flow properties and also did not address sticking and picking issues. The potential of StarTab® in enhancing flow properties and addressing sticking issues in pharmaceutical applications is highlighted. These findings contribute to optimizing formulations for efficient tablet production.